Fundamentos, experimentos e simulação de tintas térmicas para aplicação em fornos cerâmicos - Meo, Carlos Eduardo de (Universidade Federal de São Carlos, 2019)
Regarding the current need of higher sustainability and cost reductions of industrial processes, some require high amounts of energy due to the high temperatures involved being siderurgy a good example. In these scenarios thermal radiation becomes the major heat transfer process. Therefore two main routes are explored in this work: the use of high emissivity and high reflecting coatings aiming for an energy saving technology. Using these products, one of them is able to maintain the refractories bulk properties altering only the surface ones. A methodology for choosing between high reflectance or high emissivity is quite complex since the understanding of thermal optical properties relies on concepts from solid state physics and non-linear partial differential equations to model the heat fluxes. As a way of solving this issue, in this work a methodology is proposed based on attesting the efficiency of commercial coatings and numerical simulation to study high complex scenarios, where its usage is not easily available, like an industrial furnace that belongs to Saint-Gobain company. The results found in this work highlights possible gains of close to 2% using a combination of high emissivity and reflectance coatings on the furnace, but, in combination with other techniques besides coatings, possible gains close to 20%. Besides that, in this work it has been proven that there is no unanimous solution in terms of one coating over the other one. Each system is unique and the best energy saving solution might be a combination of both.
Fundamentals, experiments, and simulation of thermal coatings for application in ceramic furnaces
Keywords: Tintas térmicas; Tintas refratárias; Emissividade; Reflectância; Eficiência energética; Simulação numérica; Thermal coatings; Refractory coatings; Emissivity; Reflectance; Energy saving technology; Numerical simulation; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA